ANALISIS PENGGUNAAN MEDIA INFOGRAFIS DALAM PEMAHAMAN SISWA TERHADAP PEMBELAJARAN IPAS DI SEKOLAH DASAR - Paramita, Rina; Harmawati; Tia Latifatu Sa’diah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study is to investigate how elementary school students' comprehension is affected by the use of infographic media. Subjective examination is a utilized for this exploration. The case study approach is utilized in this kind of research. The exploration subjects were an educator and the understudy. To guarantee the truth, various methods, such as observation and interviews, were used to collect the data. Each informant is chosen with the intention of gathering the necessary information, and it is assumed that they are aware of the situation under investigation. The examination got information through: understudies I went about as essential sources, who had broad data about the inquiries posed to by the specialist. The selected students have used infographic media to learn. Educators went about as auxiliary witnesses, who upheld the data from essential sources. Infographics are visual media that join illustrations and text, making learning seriously intriguing and connecting with for understudies. The conclusion demonstrates that infographics increase students' engagement in the learning process and enhance their comprehension of the subject matter. By and large, this study shows that infographics can be valuable for understudies in essential training since they assist them with figuring out the material and participate in the growing experience.